Isolasi dan Karakterisasi Bakteri Asam Laktat (BAL) pada Sere Kedele di Kabupaten Gianyar - Sandhi Wipradnyadewi, Putu Ari; Sugitha, I Made; Wayan Gunam, Ida Bagus; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 2 (2024): Jurnal ITEPA, 2024)
Lactic acid bacteria (LAB) are found in many fermented food products. Sere kedele is a fermented soybean food produced by the people of Gianyar Regency. This study aims to isolate and characterize LAB on sere kedele in Gianyar Regency. Saturated sampling technique was used in sampling Sere Kedele in Gianyar Regency. The research results showed that there were 24 isolates that were purple in color and were LAB isolates in the form of cocci and bacilli.